PENGARUH AMELIORAN ABU JANJANG SAWIT TERHADAP PERTUMBUHAN DAN HASIL AKSESI PADI LOKAL (Oryza sativa L.) PADA LAHAN GAMBUT - Safrida Safrida; Suparman Suparman; Parman Parman (Universitas Teuku Umar, 2018)
This study aims to determine the influence of amelioran ash of spadix palm to accessions the local rice as well as real whether the interaction of these two factors on the cultivation occurring in the peat. This research was compiled in a separate Swath Design Split plot with 2 and 4 treatment groups, consisting of 4 local rice accessions, namely: Pandrah, Boh Sirutoh, Pinlago and IR-36. Factors amelioran the ash of spedix palm consists of: A0, A1 = control = 15 ton ha-1 (3.38 kg plot-1). The results showed that the real effect of accession towards high plant age 30, age 45 HST and very real effect at age 60 HST, influential real accession number of saplings against age 60 HST, but has no effect on real at the age of 30and 45 HST. Accessions take effect against the number of saplings of real productive and very influential real against the weight of grain per plot. Pandrah accessions (V1) has the ability level of the rate of growth at a high level of crop, the amount of the child, the number of saplings of productive and heavy grain keringper plot. Treatment of the amelioran ash of spedix of palm on peat, was able to increase the growth of plants at high levels, the number of chicks, the number of saplings of productive but the effect is not real against the weight of dried grain per plot.Keywords: ameliorant, ash spadix palm, local rice, peat